Асфальт: роман / Евгений Гришковец - Гришковец Евгений Валерьевич (Махаон, 2008)
Экземпляры: Селтинская районная библиотека (аб) (20091012) / Инвентарный номер: 196215 / Цена: 167.40 / Авт.знак: Г 85 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6